Early Human Colonization, Climate Change and Megafaunal Extinction in Madagascar: The Contribution of Genetics in a Framework of Reciprocal Causations - Tofanelli, Sergio; Bertoncini, Stefania; Donati, Giuseppe (Frontiers in Ecology and Evolution, 2022)
The relative importance of climate shifts and human activities on Madagascar's Holocene ecological transitions is highly contentious. Increasing evidence supports a scenario of negligible impact of climate changes on megafauna extinctions. However, a comprehensive picture can only be obtained by overcoming a dichotomic view and weighing the contributions of diverse disciplines in an integrated framework. Multidisciplinary approaches implementing genetic data reveal scenarios of higher complexity during the human colonization of the island, sometimes unevenly related to climate-driven landscape transformations. Reconstructions of Holocene demographics from the genomes of living and sub-fossil species show signs of a closer association between past population size contractions and paleo-climatic shifts. From this perspective, the main causes of the megafaunal demise likely trace back to the mutual reinforcement between the ecological shifts that followed the settlement of new immigrants and those induced by millennial climate trends.